A Comparative Study of Metadiscourse in Academic Writing: Male vs. Female Authors of Research Articles in Applied Linguistics - Nasser Ghafoori (Journal of Applied Linguistics, 2012)
Like conversation and other modes of communication, writing is a rich medium for gender performance. In fact, writing functions to construct the disciplines as well as the gender of its practitioners. Despite the significance of author gender, as one constitutive dimension of any writing, it has been relatively under-researched. One way, by means of which author gender is practiced, and revealed in written discourse, is the incorporation and use of metadiscoursal categories. Examining 20 applied linguistics research articles (10 written by native male English writers and 10 written by native female English writers), the present study sought to examine whether male and female native English writers differed in their use of metadiscoursal elements. For this purpose, Hyland’s (2005) model of metadiscourse was employed as an analytical framework to identify the type of metadiscoursal elements. The results of Independent samples t-test showed that English male and female writers did not differ significantly in their overall use of metadiscourse; but, significant differences were observed in categorical distribution of metadiscoursal elements. The findings of the study can provide a sound basis for the development of pedagogical materials.